Detection of significantly high vitreous concentrations of fatty acid-binding protein 4 in patients with proliferative diabetic retinopathy - Kaku Itoh (Nature Portfolio, 2021)
Abstract The fatty acid-binding protein4 (FABP4) and vascular endothelial growth factor A (VEGFA) play key roles in the metabolic and cardiovascular diseases, and proliferative diabetic retinopathy (PDR), respectively. To identify FABP4 in vitreous fluid in PDR, vitreous concentrations of FABP4 (V-FABP4) and VEGFA (V-VEGFA) from PDR (n = 20) and non-PDR (n = 20) patients were determined by Enzyme-Linked ImmunoSorbent Assays. The data, which included height and weight, systemic blood pressures, several blood biochemical parameters and blood flow at the optic nerve head (ONH) by laser speckle flowgraphy (LSFG) were collected. The levels of V-FABP4 and V-VEGFA were significantly higher in PDR patients than in non-PDR patients (P < 0.001) with a high positive correlation (r = 0.72, P < 0.001) between them. The findings were not affected by body mass index values and the presence of vitreous hemorrhaging. Among the clinical parameters, V-FABP4 correlated positively with creatinine and negatively with age and aspartate transaminase (AST) levels, while V-VEGFA correlated positively with fasting plasma glucose and hemoglobin A1c (HbA1c) levels but negatively with AST. Multiple regression analyses indicated that V-VEGFA, or V-FABP4, AST and HbA1c were independent predictors of V-FABP4 or V-VEGFA, respectively. Both were negatively correlated, but more evident in V-FABP4, with the ONH ocular blood flow.